Influence of lake trophic conditions on the dominant mixotrophic algal assemblages - Saad, Juan Francisco (2016)
Mixotrophic protists combine photo-autotrophy and phago-heterotrophy. Even though only in oligotrophic systems mixotrophs overcome strictly autotrophs, they are represented all along the trophic spectrum. We hypothesize that lakes with different chlorophyll a (Chla) and dissolved organic carbon (DOC) concentrations harbor different assemblages of mixotrophs. We examined the composition of mixotrophs in 24 lakes in two Patagonian regions (Argentina), with a range of conditions of Chla and DOC. The categorization of a predominant type of nutrition in each mixotroph was based on published evidence. Additionally in four lakes we analyzed the bacterivory activity of mixotrophs by performing ingestion experiments. We found potentially mixotrophic taxa in all lakes, however the assemblages varied depending on their trophic-DOC features. Primarily heterotrophic mixotrophs (e.g. chrysophytes) attained a higher proportion in oligotrophic lakes, declining towards higher trophic status. In contrast, primarily autotrophic mixotrophs (e.g. cryptophytes) dominated in eutrophic systems. Mixotrophs actively ingested bacteria in all experiments, however cell-specific grazing rates were higher in oligotrophic lakes. Mixotrophs accounted for more than half of total flagellate grazing in oligo-mesotrophic environments. Our results suggest that there is a replacement of mixotrophic taxa along a gradient of increasing trophic state, from primarily heterotrophic to primarily autotrophic mixotrophs, whereas their relative contribution to total flagellate grazing decreases.